Allele Frequency of APAF1 Mutation in Holstein Cattle in Brazil - Albertino, Lukas Garrido; Albuquerque, Ana Luísa Holanda; Ferreira, Julia Franco; Oliveira, João Pedro Marmol; Borges, Alexandre Secorun; Patelli, Thais Helena Constantino; Oliveira-Filho, José Paes (Frontiers in Veterinary Science, 2022)
APAF1 is an autosomal recessive inherited mutation, associated with Holstein haplotype 1 (HH1) and characterized by a substitution of cytosine for a thymine (c.1741C>T) in chromosome 5. The mutation causes fetal and embryonic loss, during the 60th and 200th days of gestation, and reduced conception rate. The ARMS-PCR is considered a simple and low-cost method to determine single nucleotide polymorphism (SNP) with no need for genetic sequencing of the animal genome. This study aimed to verify the allelic frequency of APAF1 mutation in Brazilian Holstein cattle. A total of 248 Holstein DNA samples (210 cows and 38 bulls) were analyzed, and synthetic genes were manufactured to validate the primers developed by the authors. All animals assessed in this study were classified as wild-type for APAF1 mutation. The primers and protocol developed for the ARMS-PCR technique work with 100% of specificity and efficiency since the amplicon formations according to the genotypes expected. In conclusion, the mutation responsible for APAF1 was not detected in the Brazilian Holstein cattle population assessed in this prevalence study, although it is not possible to affirm that APAF1 does not occur in Brazilian Holstein animals. tetra-primer ARMS PCR protocol for APAF1 mutation that has been validated here may be a relatively simple and economical method to determine the animals' genotype.